(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
It has been documented that HPWS has both positive and negative effects on employee performance. However, limited studies are affirming this view therefore the review provides a comprehensive understanding of the strengths and weaknesses of HPWS in organisations.To aim of the study is to provide a comprehensive understanding of the strengths and weaknesses in the applications of HPWS in organisations. Under the research goals, a qualitative research methodology was utilised, specifically using in-depth interviews to collect data. The target population consisted of 6 employees of the organisation studied. These individuals were purposefully selected as they possess the necessary information to assess the perceived effects of HPWS on employee performance in organisations. For data analysis, the qualitative thematic data analysis approach was employed. The usage of thematic analysis in this study is founded on its ability to offer comprehensive and compelling insights into the concept of HPWS.Based on the six-step approach of qualitative thematic analysis, the findings suggest that the combination of employee motivation and strategic human resources management practices with HPWS can enhance employee performance. Nevertheless, it has been noted that improper implementation of HPWS can result in heightened job demands and burnout among employees. Therefore, incorporating an evidence-based approach in implementing HPWS is recommended. The study has a limitation as it solely utilizes a qualitative approach, leading to constraints in terms of statistical measurement. Consequently, it is recommended for future studies to employ quantitative or mixed methods research to obtain a more comprehensive understanding of the relationship between HPWS and employee performance.This study recommends that human resource management professionals use this research as a catalyst for implementing HPWS in their organisations. It can offer valuable guidance on effectively utilising HPWS as a concept and practical approach in managing human resources within organisations.The study highlights and postulate the importance of motivation and an evidence-based approach to HPWS. The evidence-based approach can be acknowledged as a contemporary approach to human resource management in organisations.